Triiodothyronine (T3) upregulates the expression of proto-oncogene TGFA independent of MAPK/ERK pathway activation in the human breast adenocarcinoma cell line, MCF7 - Silva, Tabata M. [UNESP]; Moretto, Fernanda C. F. [UNESP]; De Sibio, Maria T. [UNESP]; Gonçalves, Bianca M. [UNESP]; Oliveira, Miriane [UNESP]; Olimpio, Regiane M. C. [UNESP]; Oliveira, Diego A. M. [UNESP]; Costa, Sarah M. B. [UNESP]; Deprá, Igor C. [UNESP]; Namba, Vickeline [UNESP]; Nunes, Maria T.; Nogueira, Célia R. [UNESP] (Archives of Endocrinology and Metabolism, 2019)
Objective: To verify the physiological action of triiodothyronine T3 on the expression of transforming growth factor α (TGFA) mRNA in MCF7 cells by inhibition of RNA Polymerase II and the MAPK/ERK pathway. Materials and methods: The cell line was treated with T3 at a physiological dose (10-9M) for 10 minutes, 1 and 4 hour (h) in the presence or absence of the inhibitors, α-amanitin (RNA polymerase II inhibitor) and PD98059 (MAPK/ERK pathway inhibitor). TGFA mRNA expression was analyzed by RT-PCR. For data analysis, we used ANOVA, complemented with the Tukey test and Student t-test, with a minimum significance of 5%. Results: T3 increases the expression of TGFA mRNA in MCF7 cells in 4 h of treatment. Inhibition of RNA polymerase II modulates the effect of T3 treatment on the expression of TGFA in MCF7 cells. Activation of the MAPK/ERK pathway is not required for T3 to affect the expression of TGFA mRNA. Conclusion: Treatment with a physiological concentration of T3 after RNA polymerase II inhibition altered the expression of TGFA. Inhibition of the MAPK/ERK pathway after T3 treatment does not interfere with the TGFA gene expression in a breast adenocarcinoma cell line.
Keywords: Breast cancer; Gene expression; Nongenomic actions; Thyroid hormone